1993
DOI: 10.1016/0925-9635(93)90264-3
|View full text |Cite
|
Sign up to set email alerts
|

CVD diamond growth mechanisms as identified by surface topography

Abstract: The surface morphologies of numerous homoepitaxial, chemical-vapour-deposition-grown diamond films have been examined by phase-sensitive optical microscopy. The layers were produced by the hot filament technique as well as by the acetylene oxygen combustion method. The {I11} and !1001 faces manifest themselves as F faces below the roughening temperature and grow via steps nucleated at three-dimensional diamond particles or at dislocations. The rate-determining step in '1111 diamond growth is a hindered surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 33 publications
3
33
1
Order By: Relevance
“…Rather than a stepped and curved surface due to stabilization in one direc-tion by (110) PBCs as expected from a first-order PBC analysis (see Fig. la), this orientation is stabilized by microfaceting [5,11]. In this respect {110} and more generally the {hhk}h> ~ orienta- tions behave just as all other orientations with Miller indices other than {hhk} h < k, as was shown on the {111} samples.…”
Section: Growth On {110} Substratesmentioning
confidence: 59%
See 1 more Smart Citation
“…Rather than a stepped and curved surface due to stabilization in one direc-tion by (110) PBCs as expected from a first-order PBC analysis (see Fig. la), this orientation is stabilized by microfaceting [5,11]. In this respect {110} and more generally the {hhk}h> ~ orienta- tions behave just as all other orientations with Miller indices other than {hhk} h < k, as was shown on the {111} samples.…”
Section: Growth On {110} Substratesmentioning
confidence: 59%
“…The orientation dependent incorporation of impurities was investigated by flame deposition of a thin epitaxial layer on a hemispherical diamond substrate with a {110} top orientation [11]. The CL image of the grown layer shown in Fig.…”
Section: Nitrogen -Vacancy Pairsmentioning
confidence: 99%
“…Blue band A luminescence from this {hhk}h<~k 6.5 mmx 9 mm was used. The position of the sample, part of the (110) zone has also been reported for an initially 1.0 mm below the flame cone, was readjusted epitaxial, flame-deposited diamond layer on a hemiseveral times during the experiment, to correct for its spherical diamond substrate [12]. It is suggested that increasing thickness during growth.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Growth of these faces, and {1 1 9}, as indicated by the dark spots in the figure. which normally proceeds by the random addition of For silicon, the stability of facets in the (110) zone and growth units at the surface [ 11], appears to be destabithe occurrence of {7 7 13} facets have been reported by lized by the development of microfacets [12]. The Gardeniers et al [13,14].…”
Section: Microscopymentioning
confidence: 99%
“…1 [2,[20][21][22]. Such step bunches originate from a pile-up of atomically high steps generated at a given step source [23].…”
Section: Macrostep Patterns On {001} Diamond Facesmentioning
confidence: 99%